Mathematical analysis of the effect of Pro72Arg polymorphism in the TP53 gene on the emergence and progression of POAG (Ukrainian Journal of Ophthalmology, 2026)
Background: Elevated intraocular pressure (IOP) is a major risk factor for primary open-angle glaucoma (POAG). Increased attention is also given to activation of apoptosis of retinal ganglion cells which results in the development of glaucomatous neuropathy and is regulated by p53. An association between the TP53 polymorphism and POAG has been reported previously.Purpose: To analyze mathematically the effect of the Pro/Arg72 polymorphism in the TP53 gene on the emergence and progression of POAG.Materials and Methods: The study group comprised 172 patients diagnosed with POAG, and the control group comprised 98 individuals without POAG. Patients underwent ophthalmological examination and Disc Damage Likelihood Scale (DDLS) grading for stage of POAG at baseline, 12 months and 24 months. Stage of POAG at presentation (Y1), IOP category at presentation (Y2), change in POAG stage over two years (Y1D) and change in IOP category over two years (Y2D) were the output variables, whereas sex, age, duration of disease, genotype, stage of POAG at presentation, and category of IOP at presentation (IOP0) were independent (input) variables used in multiple logistic regression model building. Polymorphic variants of TP53 gene were determined by real-time PCR using a TaqMan®SNP Genotyping Assay (Life Technologies, Grand Island, NY). Statistical analysis was performed using MedCalc v.15.11.0 (MedCalc Software bvba, 1993–2015).Results: The analysis revealed associations between the severity of the pathological process (measured as stage of POAG at presentation) and disease duration, and between the severity and disease genotype. Patients with p53 Pro72Arg genotype had higher odds of a severe stage of POAG compared to those with Pro72Pro genotype (p=0.01, OR = 3.5 (95 % CI=1.3-9.5). In addition, patients with p53 Arg72Arg genotype had higher odds of developing a severe stage of POAG compared to those with Pro72Pro genotype (p=0.04, OR = 3.2, 95 % CI=1.1-9.7). There were associations between the IOP category at presentation and age, disease duration and genotype: patients with p53 Arg72Arg genotype had higher odds of a more advanced IOP category compared to those with Pro72Arg or Pro72Pro genotype (p=0.04, OR = 2.64; 95 % CI=1.04-6.67). An association was also revealed between the changes in POAG stage over two years and disease duration: the odds of developing a severe stage of POAG increased more than twofold with each 1-year increase in duration of disease (p < 0.001). Men had 2.3 times lower odds of developing a more advanced category of IOP compared with women (p = 0.035).Conclusion: A relationship was revealed between the emergence of POAG and Pro72Arg polymorphism in the TP53 gene: there were increased risks for developing severe POAG and elevated IOP in heterozygous or homozygous carriers of the mutated proapoptotic allele G (72Arg).
Keywords: Primary open-angle glaucoma; Pro72Arg polymorphism in the TP53 gene; mathematical analysis; progression; intraocular pressure